Research Progress of Comprehensive Follow-up Management Strategy on the Natural History of Simultaneous, Persistent Multiple Pulmonary Ground-glass Nodules - Chengming HUANG; Yongzhao ZHOU; Yujin FANG; Yanyang LIU; Li WANG; Yu ZHUO; Daxing ZHU (Chinese Journal of Lung Cancer)
The development and change patterns as well as the disease course management of multiple ground-glass nodules (GGNs) in the lungs are currently hotspots and difficulties in clinical lung cancer research. Understanding the latest advancements in the natural history of multiple GGNs is crucial for grasping the disease variation patterns and formulating management strategies. Meanwhile, utilizing advanced methods such as intelligent follow-up management platforms makes the long-term standardized management of GGNs possible. Therefore, this article provides an overview of the latest research advancements on the natural history of multiple GGNs and new experience in GGNs management.